2019
DOI: 10.1523/eneuro.0401-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Self-Administration Elicits Sex-Related Changes in Postsynaptic Glutamate Transmission in the Prefrontal Cortex

Abstract: Preclinical and clinical research has shown that females are more vulnerable to the rewarding effects of stimulants, and it has been proposed that estrogens may play a role in this enhanced sensitivity; however sex differences in methamphetamine (METH)-induced neuroplasticity have not been explored. To address this gap in knowledge, we recorded from the prelimbic area of the prefrontal cortex (PL-PFC) of male and female rats following long access METH self-administration (SA) and investigated the resulting lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 43 publications
13
28
1
Order By: Relevance
“…Glutamate is the major excitatory neurotransmitter in the mammalian central nervous system. In the rat PFC, males have higher baseline spontaneous glutamate release compared to females (Pena-Bravo et al 2019), which is consistent with findings in human PFC (O'Gorman et al, 2011). However, frontal cortex tissue concentration of glutamate levels in rats do not show sex differences (Zhang et al, 2018).…”
Section: Basal Sex Differencessupporting
confidence: 85%
“…Glutamate is the major excitatory neurotransmitter in the mammalian central nervous system. In the rat PFC, males have higher baseline spontaneous glutamate release compared to females (Pena-Bravo et al 2019), which is consistent with findings in human PFC (O'Gorman et al, 2011). However, frontal cortex tissue concentration of glutamate levels in rats do not show sex differences (Zhang et al, 2018).…”
Section: Basal Sex Differencessupporting
confidence: 85%
“…Memory for spatial recognition is primarily mediated by the hippocampus, especially dCA1. Consistent with the hyper-glutamatergic states found in striatum 8 , prefrontal cortex 24 and nucleus accumbens 1 by METH use, we found that extracellular Glu concentrations in the dCA1 consistently kept at high levels, and dCA1 pyramidal neurons were strongly activated in METH withdrawal mice. To assess the relationship of dCA1 Glu hyperactivity and the spatial memory deficits in METH withdrawal mice, EA at acupoints of Yintang (GV29) and…”
Section: Meth Withdrawal Causes a Hyper-glutamatergic State At Dca1 Ssupporting
confidence: 85%
“…Both sexes are included in these studies because differences occur in metabolism 29 and acquisition of drug self-administration 30,31 , and in basic and synaptic excitatory transmission 11,32 . However, our behavioral endpoint, cued reinstatement, is not sensitive to sex as a biological variable 33,34 unless the response ratio is increased during the reinstatement test 33 .…”
Section: Methodsmentioning
confidence: 99%
“…The medial prefrontal cortex (mPFC) is one of the main structures regulating relapse 5 with glutamatergic corticostriatal projections at the forefront of addiction neurocircuitry 6,7 . Meth causes enduring changes within the mPFC including augmented burst firing within glutamatergic neurons 8 , changes in extracellular glutamate concentrations 8,9 , increased NMDA receptor expression, and adaptations in pre and post synaptic glutamate transmission 911 . Anatomically, projections from the mPFC to the nucleus accumbens (NA) have a distinct dorsal-ventral anatomical distribution 12 .…”
Section: Introductionmentioning
confidence: 99%